Solar PV based seventeen level reduced switch symmetrical multilevel inverter topology fed induction motor - Gajula, Ujwala; Manivannan, Kalpanadevi; Reddy, Nomula Malla (Institute of Advanced Engineering and Science, 2024)
Multilevel inverters have received a lot of interest in recent years due to their ability to deliver more voltage levels than typical two-level inverters. Because of this property, multilevel inverters can produce output waveforms that closely resemble sinusoidal waveforms, lowering harmonic distortion dramatically. The emergence of reduced switch symmetrical multilevel inverter topologies has developed the curiosity of many different power conversion systems. These new topologies offer numerous advantages, including greater output voltage quality, fewer harmonic distortions, and increased power conversion efficiency. The inclusion of these inverters in the feeding of induction motors is one of their many prominent uses. A 17 levels of multi-level inverter (MLI) topology is presented with reduced switch count and harmonic reduction for power quality improvement. The inverter is fed by isolated equal photovoltaic panels which act as direct current or DC source. To reduce complexity, switching pulses are generated using hybrid pulse width modulation technique which is designed as controller. Through the use of MATLAB/Simulink, the performance assessment of a unique cascaded multilevel inverter-based reduced switch symmetrical inverter feeding an induction motor drive has been verified. The harmonic distortion with reduced switches obtained is 7.47% which is comparatively less than when compared with conventional cascaded H-bridge topology.